Seasonal Decomposition of Sexual Victimization-Related Cases in Hyderabad, Pakistan: Sexual Victimization-Related Cases in Hyderabad - Rasheed, Aisha; Munir, Ummara; Aslam, Nadia; Samad, Abdul; Shaikh, Muhammad Rafique; Bibi, Ishrat (Pakistan Journal of Health Sciences, 2024)
The issue of sexual assault is a serious concern that contributes to abuses of human rights and risks to public health. Evaluating situations like these is absolutely necessary in order to make the judicial process easier for both the victim and the person who committed the crime. When the seasonality of sexual assault-related incidents is determined, it can provide the community and law enforcement authorities with information that can help them implement preventative measures. Objective: To assess the seasonality of sexual assault-related cases at casualty department of a teaching hospital in Hyderabad, Pakistan. Methods: In current descriptive/prospective study, ninety two sexual assault-related medico-legal cases (MLCs) were included. This study based on the seasonality of sexual assault-related MLCs using seasonal decomposition of three-year from January 2020 to December 2022 data from a leading tertiary care teaching hospital in the Hyderabad region. Results: Most of the cases (N=42) were reported in the year 2021. The percentage of sexual assault-related MLCs was found to be concentrated from June to August (10.86% to 14.13%). The highest number of sexual assault-related MLCs occurred in July. The seasonal decomposition also showed pronounced peaks in summer, with intense peaks in July for rape and total sexual assault cases. Conclusions: The number of sexual assault-related cases was aggregated in mid-year, showing a higher trend in summer season. Efficient preventive measures in certain seasons and education of vulnerable groups can minimize sexual violence in the community